Radiation Induced F1 Sterility in Plutella xylostella (Lepidoptera: Plutellidae): Potential for Population Suppression in the Field - Nguyen Thi Quang Hoa (Florida Entomological Society, 2022)
The potential of using F1 sterility in a system to manage the diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), was investigated in the laboratory and in field-cages. When 6-day old male pupae were treated with 200 Gy of gamma radiation, 71.5% developed into normal adults. However, radiation-induced reductions in fecundity and viability were expressed during the P1, F1 and F2 generations. Sterility exceeded 60% in the P1 and F2 generations and 90% in the F1 generation. The sex ratio was skewed in favor of males among F1 and F2 progeny. The percentages of metaphase spermatogonial cells with chromosomal aberrations were 86.9, 21.5 and 9.7 in the F1, F2, and F3, respectively. No differences were observed in the sperm transfer between irradiated and unirradiated males. When treated males were released into field-cages at either a 5:1 or a 10:1 overflooding ratio with unirradiated moths, there was a significant reduction in the number of F1 and F2 adults emerging in the field-cages as compared to the control. A 50-60% reduction in the F1 and 59-68% in the F2 generation were observed. When irradiated females and males were released at a 5:5:1:1 overflooding ratio with untreated DBM, the decrease in F1 adult emergence was not significantly different than for the control. However, adult emergence in the F2 generation was reduced by almost 90%. This degree of suppression was significantly greater than that achieved in cages where only irradiated males had been released. The use of F1 sterility in combination with releases of the parasitoid, Cotesia plutellae (Kurdjumov) (Hymenoptera: Braconidae), in field-cages resulted in a 40% decrease in the DBM population in the F1 and more than 90% in the F2 generation. Nevertheless, additional research is needed to develop this system into an economically feasible strategy for managing early season populations of DBM.